The Effects of Capture and Time Out of Water on Sablefish (Anoplopoma fimbria) Reflexes, Mortality, and Health - Cara Rodgveller; Christiane V. Löhr; John A. Dimond (Journal of Marine Science and Engineering, 2021)
It is unknown if capture coupled with time out of water on-deck affect sablefish (Anoplopoma fimbria) health and reflexes, and whether it contributes to acute or delayed mortality. In this study, 35 sablefish were caught using hook-and-line gear and given six reflex tests after capture. Thirty-two were subsequently transported to the laboratory, held for 45–52 days, and then experimentally held out of the water for either 0, 3, 6, or 11 min. After 7–10 days of holding in the laboratory after the experiment, to monitor for mortalities, reflexes were tested for a second time and necropsies and histopathology were performed. There were no histological findings and no mortalities; however, parasites and minor inflammation were observed. All occurrences were not a result of capture or experiments. Some reflexes were absent after capture (77% could right themselves, 69% responded to a tail grab, and 57% responded to sound.) The only test where the reflex did not improve to 100% in the laboratory was the sound reflex. The sound reflex was highest for control fish (63%) and there were no positive sound reflexes for fish held out of water for 11 min. The absence of reflexes may result in predation after release and present issues with feeding or communication.